The effect of cold compress application on pain in post-hemorrhoidectomy patients - Diyanto, Velani Prastika; Rosyid, Fahrun Nur (Science Midwifery, 2024)
Postoperative pain is a common complication after hemorrhoidectomy, and cold compresses have been used as a non-pharmacological intervention to manage this pain. This systematic review aimed to evaluate the effect of cold compress application on pain reduction in post-hemorrhoidectomy patients. The review was conducted according to PRISMA guidelines, with searches performed in electronic databases such as PubMed, Scopus, and Google Scholar for articles published in the past ten years. Inclusion criteria encompassed studies comparing cold compresses with other methods or control groups, with pain measurements primarily using the visual analog scale (VAS). Out of 150 initially identified articles, 10 met the inclusion criteria. The findings indicate that cold compress application significantly reduces postoperative pain compared to control groups. Cold compresses are thus a viable intervention for pain management following hemorrhoidectomy, though further research with stronger designs and larger sample sizes is recommended to confirm these results.